Konsekuensi Hukum atas Transaksi Berdasarkan PPJB dalam Jual Beli Hunian Superblok - Reza, Muhammad; Fuad, Fokky (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study examines the legal consequences in the Binding Purchase and Sale Agreement of superblock housing by development companies. PPJB made by Buntario Tigris Notary in Central Jakarta does not clearly detail the time period for the issuance of the Deed of Sale and Purchase as per Article 5 (Development Completion) and Article 6 (Physical Delivery). PPJB has been ratified by PT Elite Prima Hutama as a standard agreement for investors who are interested in investing in superblock housing developed by the company. The Deed of Sale and Purchase (AJB) can change the rights and obligations of law No. 7 of 2021 concerning the Harmonization of Tax Regulations. What are the legal consequences for PPJB that does not explain the time period for the issuance of the Sale and Purchase Deed. This research is a normative legal research with secondary data in the form of PPJB documents on the Superblock residential project. This study analyzes what legal consequences can be experienced by investors from the legal events of the Sale and Purchase Agreement due to the absence of a clause that regulates the time period for the issuance of the sale and purchase deed. On the other hand, this study also reviews how the legal relationship of PPJB to legislation. By using the Civil Code as a legal framework and PPJB as a legal product, the results of this study confirm what legal consequences can be experienced by investors and what legal remedies can be taken to protect the rights to the obligations of the provisions of PPJB Article 3 (1) (Repayment) because there is no clause that explains in detail related to the issuance of a Sale and Purchase Deed.